Analisis Kinerja Pelayanan Kesehatan Tenaga Medis Di Puskesmas Air Besar Negeri Batu Merah Kecamatan Sirimau Kota Ambon Provinsi Maluku - Sukma Muhammad; Iriane Sosiawaty Ponto; Julia Theresia Patty (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research is a qualitative descriptive research. Aims to analyze and explain the Analysis of Health Service Performance of Medical Personnel at Puskesmas Air Besar, Batu Merah Village, Sirimau District, Ambon City, Maluku Province. Informants in this study amounted to 6 people. Data collection techniques used are observation, interviews and documentation and analysis techniques using the interactive analysis model from Miles and Huberman, namely conducting data reduction, presenting data and drawing conclusions. The results of this study indicate that the Analysis of Health Service Performance of Medical Personnel at the Air Besar Health Center, Batu Merah Village, Sirimau District, Ambon City, Maluku Province, is effective but not optimal. The five indicators are influenced by the quality factors of health service performance at the community health center (Puskesmas).